If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (25 + -5y) = 4x + -9y + 13 Remove parenthesis around (25 + -5y) 25 + -5y = 4x + -9y + 13 Reorder the terms: 25 + -5y = 13 + 4x + -9y Solving 25 + -5y = 13 + 4x + -9y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '9y' to each side of the equation. 25 + -5y + 9y = 13 + 4x + -9y + 9y Combine like terms: -5y + 9y = 4y 25 + 4y = 13 + 4x + -9y + 9y Combine like terms: -9y + 9y = 0 25 + 4y = 13 + 4x + 0 25 + 4y = 13 + 4x Add '-25' to each side of the equation. 25 + -25 + 4y = 13 + -25 + 4x Combine like terms: 25 + -25 = 0 0 + 4y = 13 + -25 + 4x 4y = 13 + -25 + 4x Combine like terms: 13 + -25 = -12 4y = -12 + 4x Divide each side by '4'. y = -3 + x Simplifying y = -3 + x
| 7(x+1)=4[x-3(3-x)] | | 5(x-12)= | | -6(1+2k)=-6-4k | | 2(4+20-1)= | | n+.6=n | | -3(2X-1)+5=50 | | 1+8n+5=-2 | | (3)(2)(-30)= | | 10x-3=5x+10 | | -14x+5y=19 | | 4(b-6)=71-2b | | 15+18-12=x | | 10p(1+9p)=8p^2 | | .667x+5=4 | | 8+20(3x+1)= | | 12x-8=8x-28 | | 2x-27-10=16 | | 4+x+3= | | x*5x=20 | | 2m+5=5m-7-5m | | -10x+2=10 | | 4x^2+10x=x+8 | | -10(-v+3)+6(v-11)=v+3+6 | | 54=4x^2-2X-2 | | (6x+2)=(5x+7) | | b*5a=20 | | 3(x+1)=5x-6 | | 4x+7=2-(8x-8) | | 2x+4y+6y-3xy=0 | | 5t+(2t-1)+t=27 | | 26+12-18=x | | 3x(x^2+9)=0 |